Cell Cycle Dysregulation and Renal Fibrosis - Yun-Shan Wu (Frontiers Media S.A., 2021)
Precise regulation of cell cycle is essential for tissue homeostasis and development, while cell cycle dysregulation is associated with many human diseases including renal fibrosis, a common process of various chronic kidney diseases progressing to end-stage renal disease. Under normal physiological conditions, most of the renal cells are post-mitotic quiescent cells arrested in the G0 phase of cell cycle and renal cells turnover is very low. Injuries induced by toxins, hypoxia, and metabolic disorders can stimulate renal cells to enter the cell cycle, which is essential for kidney regeneration and renal function restoration. However, more severe or repeated injuries will lead to maladaptive repair, manifesting as cell cycle arrest or overproliferation of renal cells, both of which are closely related to renal fibrosis. Thus, cell cycle dysregulation of renal cells is a potential therapeutic target for the treatment of renal fibrosis. In this review, we focus on cell cycle regulation of renal cells in healthy and diseased kidney, discussing the role of cell cycle dysregulation of renal cells in renal fibrosis. Better understanding of the function of cell cycle dysregulation in renal fibrosis is essential for the development of therapeutics to halt renal fibrosis progression or promote regression.